Pelatihan Pembuatan Lulur Tradisional Daun Kelor dengan Kombinasi Kulit Jeruk pada Kelompok Ibu – Ibu Pemberdayaan dan Kesejahteraan Keluarga - Indriastuti, Marlina; Silfia, Risa; Novianty, Elisa; Dwi Elianti, Adis; Trilianti, Shindi; Yuliawati, Siti; Harun, Nurhidayati; Kurniasih, Nia (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Lulur is a cosmetic care product used to treat and cleanse the skin of dirt and remove dead skin cells, made from moringa leaves and a combination of lime peel rough texture that is used by applying and rubbing slowly to the surface of the skin. Objective: the purpose of this extension activity is to improve the understanding and skills of the PKK mother Group in Batumalang Village regarding the processing of (moringa leaves) into traditional scrub products. The target of this service is the PKK mother Group on May 30, 2025 in Batumalang Village, Cimerak District, Pangandaran Regency. Method: counseling on making traditional scrub from (moringa leaves). Training on how to make a traditional scrub from (moringa leaves) with a certain formulation so that it can be done at home. Result: this extension activity was attended by PKK mothers in Batu malang Village, Cimerak District, Pangandaran Regency, which amounted to 17 people. Society. Implementation of training to PKK mothers in the manufacture of body scrub made from (moringa leaves) with a combination of lime peel, providing benefits to the skin, the community is very enthusiastic about this training activity on the use of body scrub made from natural ingredients. Conclusion: based on the results of the study it can be concluded that the preparation of (moringa leaf) scrub with a combination of lime peel that has been made can be used as a treatment to brighten and moisturize the skin.